Aspects of the morphological radiographic and ultrasonographic anatomy of the red panda (Ailurus fulgens) and ring-tailed lemur (Lemur catta) - Groenewald, Hermanus B. (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2015.